An Effort to Increase Public Financial Literacy through the Use of M-Banking: Case Study of Bank Mandiri Surabaya Branch - Ilmi, Dita Rohmatul; Taufiq, Muhammad; Utami, Anisa Fitria (Pascasarjana Universitas Mataram, 2025)
Improving people's financial literacy using m-banking is crucial in today's digital era, where around 70% of Indonesians still have a low level of financial literacy. This research focuses on Bank Mandiri Surabaya Branch, where more than 60% of customers do not fully understand the use of digital banking services, especially m-banking. This community service activity aims to improve customers' understanding of m-banking and its benefits in financial management. Using training modules and hands-on demonstrations, participants were taught how to download applications, conduct transactions, and understand important features in m-banking. Results showed that the education significantly improved customers' understanding and confidence in using the m-banking application. Participants reported an increased interest in applying the new knowledge in their daily financial management. This program not only contributes to the improvement of individual financial literacy but also promotes broader financial inclusion in the community. Thus, this activity confirms the importance of structured and practical education to improve financial literacy and utilize digital banking technology effectively.